Negotiating Mathematical Meaning in Digital Spaces: A Systematic Review of Paul Ernest’s Social Constructivism in Mathematics Education - Mohammad Nurwahid; Sofia Ashar (Universitas Islam Lamongan, 2026)
The rapid development of digital technologies has transformed mathematics education by enabling new forms of interaction, communication, and collaboration in learning environments. However, many studies still emphasize instructional strategies without explicitly examining the epistemological process through which mathematical meaning is constructed. This study aims to systematically review on Paul Ernest’s social constructivism with a specific focus on the negotiation of mathematical meaning in digital learning spaces. This study employs a systematic review design following a structured review protocol that includes formulation of research questions, systematic search of relevant literature, selection based on inclusion and exclusion criteria, quality appraisal, and thematic synthesis. A total of 28 peer reviewed studies published between 2019 and 2025 were selected from reputable databases focusing on social constructivism, digital mathematics education, and technology enhanced learning. The data were analyzed using thematic analysis to identify patterns related to epistemological foundations, meaning negotiation processes, digital learning environments, teacher student roles, and implementation challenges. The findings are organized into five key themes: epistemological foundations of social constructivism, negotiation of mathematical meaning in learning processes, digital environments as spaces for meaning construction, transformation of teacher and student roles, and challenges and opportunities in digital constructivist learning. The synthesis shows that mathematical knowledge is consistently conceptualized as socially constructed through interaction, discourse, and collaborative reasoning. The results further indicate that digital environments expand the space for mathematical meaning negotiation by enabling multimodal representations, distributed interaction, and technology mediated communication. Nevertheless, the effectiveness of these environments depends on digital literacy, pedagogical design, and interaction quality. Teachers play a crucial role as facilitators of epistemic environments, while students actively construct and validate mathematical knowledge through collaborative engagement.